Monday

September 1, 2014

September 1, 2014

Posted by **Anonymous** on Friday, March 25, 2011 at 7:17pm.

- calculus -
**Reiny**, Friday, March 25, 2011 at 7:58pmuse the product rule

f'(s) = x^2(-sinx/cosx) + 2x(cosx)

= -x^2(tanx) + 2x(cosx)

**Answer this Question**

**Related Questions**

Math, Calculus - Find the derivative of the function. y= xcosx - sinx What's the...

calculus - For a function f, let f*(x) = lim as h→0 be [f(x+h) - f(x-h)]/h...

calculus help - Find the derivative of the function. y = integral from cosx to ...

Calculus - If f(x)=4sinx/1+cosx then f'(x)=_____? I think that the derivative of...

Calc - 1. Differentiae each function a) Y=-3x^2+5x-4 b) F(x) = 6/x-3/x^2 c) F(x...

Calculus - How would I find the antiderivative of this equation? S 0 to pi/3 (1-...

AP Calculus AB - Find the derivative of: y=(cosx)^3-(sinx)^3

Calculus - How do you find the derivative of: y= 2sinx cosx

calculus help - find the derivative of the function integral from cosx to sinx (...

calculus - Find derivative(use logrithmic functions). y=x^-cosx